2010
DOI: 10.4137/oed.s2821
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cellular Inclusions in Bietti’s Crystalline Dystrophy

Abstract: Bietti’s crystalline dystrophy (BCD) consists of small, yellow-white, glistening intraretinal crystals in the posterior pole, tapetoretinal degeneration with atrophy of the retinal pigment epithelium (RPE) and “sclerosis” of the choroid; in addition, sparking yellow crystals in the superficial marginal cornea are also found in many patients. BCD is inherited as an autosomal-recessive trait (4q35-tel) and usually has its onset in the third decade of life. This review focuses on the ultrastructure of cellular cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Transmission electron microscopy (TEM) observations confirmed that NOR iPSC-RPE cells grew as a monolayer of highly polarized cells with abundant apical microvilli and melanosomes, whereas BCD iPSC-RPE cells exhibited accumulations of melanosomes and autophagosomes and intracellular pigmented granules and vacuolated cytoplasm ( Fig. 1 F ) that recapitulated RPE changes reported in BCD patients ( 16 ). To better characterize the phenotype of iPSC-RPE cells, we evaluated the growth rate and cell death rate of iPSC-RPE progenitor cells ( Materials and Methods ).…”
Section: Resultssupporting
confidence: 64%
“…Transmission electron microscopy (TEM) observations confirmed that NOR iPSC-RPE cells grew as a monolayer of highly polarized cells with abundant apical microvilli and melanosomes, whereas BCD iPSC-RPE cells exhibited accumulations of melanosomes and autophagosomes and intracellular pigmented granules and vacuolated cytoplasm ( Fig. 1 F ) that recapitulated RPE changes reported in BCD patients ( 16 ). To better characterize the phenotype of iPSC-RPE cells, we evaluated the growth rate and cell death rate of iPSC-RPE progenitor cells ( Materials and Methods ).…”
Section: Resultssupporting
confidence: 64%
“…3C, arrow ). 18, 19 Better-preserved retina temporally with less abnormal SW- and NIR-FAF signals showed a near normal retinal lamination with only an occasional hyperreflective lesion within the RPE (Fig. 3C, right panels, star ).…”
Section: Resultsmentioning
confidence: 98%
“…Cone and rod photoreceptors are equally affected in many cases with BCD and therefore central vision drops even at early stages of the disease in some cases [ 2 ]. In addition to evolving disease process already compromising the macular function several rare macular changes may further decrease the visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Bietti's crystalline dystrophy (BCD) is likely related to aberrant oxidation of cellular lipid metabolism [ 2 ] which is caused by mutations of the CYP4V2 gene, a member of the cytochrome P450 genes [ 3 ], and the dystrophy can be familial [ 4 , 5 ]. Hallmark of the disease is the presence of intraretinal crystals mostly located paracentrally and the crystals particularly lie at the transition zone between relatively normal and atrophic retinal pigment epithelium [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%